PAIN TREATMENT SERVICE AND BASIC MANAGEMENT PAIN TRAINING FOR COMMONS AND MEDICAL PERSONNEL IN SURABAYA - Arie Utariani; Soni Sulistiawan; Robby Dwestu Nugroho; Herdiani Sulistyo Putri (Jurnal Layanan Masyarakat (Journal of Public Services), 2023)
Pain is an unpleasant sensory and emotional experience associated with actual or potential tissue damage. The lack of up-to-date basic knowledge of pain management, especially among healthcare professionals in Primary Health Care Facilities in Surabaya, often leads to the perception that pain is trivial and consequently inadequately addressed. The objective of this social service activity in pain treatment and basic pain management training is to provide appropriate treatment for the community's pain scale and impart current knowledge on pain management that can be applied in daily practice by healthcare professionals and the general public in Surabaya. This initiative involves two methods: treating pain in non-medical community members and providing basic pain management training for healthcare professionals. Examination and anamnesis are conducted for each patient according to the examination questionnaire, which includes the Pain Questionnaire for Laypersons, the Physical Examination Form for Pain Management Social Service, and the Quality of Life Scoring. The initial examination and anamnesis results will determine whether the patient falls into the acute or chronic pain category, allowing for tailored interventions based on patient grouping. As for the basic pain management training, it is conducted by a pain management consultant, comprising the Socialization of the Pain Management Center, a General Lecture on the New Paradigm of Pain Management in the Community, and a Hands-On Pain Management Workshop for patients in pain.